2014
DOI: 10.1007/s00405-014-2909-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of radiofrequency ablation in the treatment of sleep disordered breathing: a meta-analysis

Abstract: Radiofrequency ablation (RFA) is used in the treatment of sleep disordered breathing (SDB), particularly in the alleviation of snoring. The literature provides evidence that the short-term results are promising; however, the long-term efficacy is a matter of contention. In this article, we present the results of a literature search of studies that use RFA in the treatment of SDB which have a follow-up time of greater than a year. RFA was found to be a safe technique with minimal morbidity. The overall Visual A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Currently, radiofrequency applications to the soft palate have shown promising long-term efficacy and has been approved by NICE in the UK (57). Repeat procedures may be required but complication rates are low (58). Additional tonsillectomy may also be beneficial either at a primary or secondary stage, depending on clinical findings and DISE evaluation.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Currently, radiofrequency applications to the soft palate have shown promising long-term efficacy and has been approved by NICE in the UK (57). Repeat procedures may be required but complication rates are low (58). Additional tonsillectomy may also be beneficial either at a primary or secondary stage, depending on clinical findings and DISE evaluation.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…tonsillectomy and resection of redundant tonsillar pillars, or shortening of uvula. Repeat applications may be required, but nevertheless complication rates remain low [ 41 ]. These include mucosal ulceration, although abscess/fistula has also been reported.…”
Section: Surgical Managementmentioning
confidence: 99%
“…This subsequently causes local tissue heating, cell necrosis, and scarring. Histological studies have identified that the lesion spreads from the probe to an 8mm circumference [4]. This has the distinct advantage of providing therapeutic tissue necrosis in the interstitial layer but keeping the mucosal layer largely unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency can be used to fibrose tissue but also as a cutting technique with minimal collateral damage [6]. Radiofrequency acts without stimulating nerves and muscle, which allows it to be used without general anaesthetic in the clinic setting [4].…”
Section: Introductionmentioning
confidence: 99%